Blood pressure distribution and control in coronary patients from 24 European countries in the European Society of Cardiology EURoObservational Research Programme European survey of cardiovascular disease prevention and diabetes. EUROASPIRE IV Registry. Issue 10 (October 2019) - Cífková, Renata; Lánská, Věra; Bruthans, Jan; Mayer, Otto; Kotseva, Kornelia; Wood, David; Lovic, Dragan; De Sutter, Johan; Reiner, Zeljko; Fras, Zlatko; Deckers, Jaap; Gotcheva, Nina; et al.
Abstract : Background: Hypertension is the most prevalent major independent risk factor for developing coronary heart disease (CHD). The present analysis aimed to assess blood pressure (BP) distribution and factors associated with insufficient BP control in coronary patients from 24 countries participating in the European Society of Cardiology (ESC) EURoObservational Research Programme (EORP) EUROASPIRE IV survey. Methods: EUROASPIRE IV is a cross-sectional study conducted in 2012–2013 in patients aged 80 years or less hospitalized for CHD with a follow-up visit at a median of 16 months later. Logistic regression analysis was applied to confirm factors associated with BP control defined as less than 140/90 mmHg for nondiabetic patients and less than 140/85 mmHg for diabetic patients. Results: A total of 7998 patients (response rate, 48.7%) attended the follow-up visit. Complete data were available in 7653 participants (mean age 62.5 ± 9.6 years). The BP goal was achieved in 57.6%. Patients failing to achieve the BP goal were older, had higher BMI, had more often a history of coronary artery bypass grafting (CABG) and reported diabetes more frequently. Logistic regression confirmed the following independent significant predictors of not achieving the BP goal: a history of diabetes [odds ratio (OR) 1.75], obesity (OR 1.70 vs. normal BMI), overweight (OR 1.28 vs. normal BMI), age at least 65 years (OR 1.53) and CABG as the index event (OR 1.26 vs. acute MI). Conclusion: EUROASPIRE IV found insufficient BP control in a large proportion of patients with stable CHD, with diabetes, increased BMI, older age and CABG as the index event being independent predictors of poor BP control. Abstract : Supplemental Digital Content is available in the text